2019
DOI: 10.1016/j.diabet.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in patients with diabetic nephropathy

Abstract: In DN patients, the complement system is activated and, of the three possible complement pathways, activation of the lectin and alternative pathways is associated with renal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
(15 reference statements)
3
66
2
Order By: Relevance
“…It should be pointed out that the present finding of a close correlation between urinary CAPs and renal tubular interstitial injury is quite different from the results obtained by Li et al . For the present, we cannot explain the causes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It should be pointed out that the present finding of a close correlation between urinary CAPs and renal tubular interstitial injury is quite different from the results obtained by Li et al . For the present, we cannot explain the causes.…”
Section: Discussioncontrasting
confidence: 99%
“…reported urinary CAP levels in 50 biopsy‐proven DN patients. However, with the mean eGFR being 44.28 mL/min/1.73 m (44.28 ± 26.79 mL/min/1.73 m) and mean proteinuria being 6.33 g/24 h (6.33 ± 4.35 g/24 h), most of the patients included in the study by Li et al . still belonged to the advanced stage of DN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether this is the result of complement deposition on severely damaged tissues or secondary complement deposition directly accelerates kidney injury caused by diabetic injury is yet to be clarified. Several studies have shown that glomerular complement split products are seen in patients with DN, and the complement system may have a role in disease process …”
Section: Discussionmentioning
confidence: 99%